Modeling the Impacts of Local Factors for Healthcare Building Energy Performance Improvement in Thailand - Nuttasit Somboonwit; Nopadon Sahachaisaeree (My University, 2018)
This research aims to perform, compare, and evaluate Integrated Building Design (IBD) processes, collaborating the Building Information Modeling (BIM) with Building Performance Simulation (BPS) applications to perform energy analysis and to improve the building energy performance of a Generalizable Building Design (GBD), a universal application on health care facilities design in Thailand. The IBD processes produce the simulation results in a harmonious direction. Slight variation in building orientation could alter the extent of energy consumption. The integration of the three measures could minimize energy consumption greatly. The study addresses the limitations of the IBDs in the software integration processes.
Keywords: Building Information Modeling; Consumption; Building Design; Energy Efficiency and Management